1992
DOI: 10.1007/bf01962533
|View full text |Cite
|
Sign up to set email alerts
|

Current status of interferon alpha in the treatment of chronic hepatitis B

Abstract: Interferon alpha is the only available therapy for patients with chronic hepatitis B. With interferon alpha 3-15 MU thrice weekly or 5 MU daily during 3-6 months one-third of the patients achieve seroconversion of HBeAg and HBV-DNA together with normalization of aminotransferases and slight improvement of histology. Loss of HBsAg is reported in a minority of responders during treatment, but increases during follow-up. Patients with baseline alanine aminotransferase of at least twice the upper limit of normal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The word diet , for children or adolescents, can embrace several unhealthy eating habits therefore the concept was explained to the participants before filling in the questionnaire. Self-esteem was calculated through the Multidimensional Self Concept Scale (MSCS) proposed and validated by Braken [18] and being part of a review on self-esteem scales for Children and Adolescents [19]. This 150-item self-report scale assesses global self-concept as a composite of six environmental contexts (domains): Social, Competence, Affect, Academic, Family and Physical.…”
Section: Methodsmentioning
confidence: 99%
“…The word diet , for children or adolescents, can embrace several unhealthy eating habits therefore the concept was explained to the participants before filling in the questionnaire. Self-esteem was calculated through the Multidimensional Self Concept Scale (MSCS) proposed and validated by Braken [18] and being part of a review on self-esteem scales for Children and Adolescents [19]. This 150-item self-report scale assesses global self-concept as a composite of six environmental contexts (domains): Social, Competence, Affect, Academic, Family and Physical.…”
Section: Methodsmentioning
confidence: 99%
“…There are many studies which are dealing with the treatment of chronic HBV infection where different type, dose and duration of INF has been used. Early studies showed that a thrice weekly or daily schedule <3 months was ineffective and recurrences of viral replication were observed after cessation of IFN [15,25]. Individual patient data from 10 clinical controlled trials showed that IFN administered at a dose of 15–30 Million Unit (MU) per week should be considered effective after 1–2 months of treatment [26].…”
Section: Different Modalities For the Treatment Of Chronic Hepatitis mentioning
confidence: 99%
“…The main goals of antiviral therapy [6,10,13,15] are to: • eradicate the virus or to convert patients from a high replicative phase to a low one (HBeAg seroconversion to anti-HBe with loss of detectable serum HBV-DNA); • provide normal or lowered ALT levels;…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations